# Solve for w 1/d=1/p+1/w 1d=1p+1w
Rewrite the equation as 1p+1w=1d.
1p+1w=1d
Subtract 1p from both sides of the equation.
1w=1d-1p
Find the LCD of the terms in the equation.
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
w,d,p
Since w,d,p contain both numbers and variables, there are two steps to find the LCM. Find LCM for the numeric part 1,1,1 then find LCM for the variable part w1,d1,p1.
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.
1
The factor for w1 is w itself.
w1=w
w occurs 1 time.
The factor for d1 is d itself.
d1=d
d occurs 1 time.
The factor for p1 is p itself.
p1=p
p occurs 1 time.
The LCM of w1,d1,p1 is the result of multiplying all prime factors the greatest number of times they occur in either term.
w⋅d⋅p
Multiply wd by p.
wdp
wdp
Multiply each term by wdp and simplify.
Multiply each term in 1w=1d-1p by wdp in order to remove all the denominators from the equation.
1w⋅(wdp)=1d⋅(wdp)-1p⋅(wdp)
Cancel the common factor of w.
Factor w out of wdp.
1w⋅(w(dp))=1d⋅(wdp)-1p⋅(wdp)
Cancel the common factor.
1w⋅(w(dp))=1d⋅(wdp)-1p⋅(wdp)
Rewrite the expression.
dp=1d⋅(wdp)-1p⋅(wdp)
dp=1d⋅(wdp)-1p⋅(wdp)
Simplify each term.
Cancel the common factor of d.
Factor d out of wdp.
dp=1d⋅(d(wp))-1p⋅(wdp)
Cancel the common factor.
dp=1d⋅(d(wp))-1p⋅(wdp)
Rewrite the expression.
dp=wp-1p⋅(wdp)
dp=wp-1p⋅(wdp)
Cancel the common factor of p.
Move the leading negative in -1p into the numerator.
dp=wp+-1p⋅(wdp)
Factor p out of wdp.
dp=wp+-1p⋅(p(wd))
Cancel the common factor.
dp=wp+-1p⋅(p(wd))
Rewrite the expression.
dp=wp-1⋅(wd)
dp=wp-1⋅(wd)
Rewrite -1(wd) as -(wd).
dp=wp-wd
dp=wp-wd
dp=wp-wd
Solve the equation.
Rewrite the equation as wp-wd=dp.
wp-wd=dp
Factor w out of wp-wd.
Factor w out of wp.
w(p)-wd=dp
Factor w out of -wd.
w(p)+w(-1d)=dp
Factor w out of w(p)+w(-1d).
w(p-1d)=dp
w(p-1d)=dp
Rewrite -1d as -d.
w(p-d)=dp
Divide each term by p-d and simplify.
Divide each term in w(p-d)=dp by p-d.
w(p-d)p-d=dpp-d
Cancel the common factor of p-d.
Cancel the common factor.
w(p-d)p-d=dpp-d
Divide w by 1.
w=dpp-d
w=dpp-d
w=dpp-d
w=dpp-d
Solve for w 1/d=1/p+1/w     